How discrete emotions affect misinformation reported in eyewitness testimonies - Sharveena Devi Daniel Mahendran; Quek, Ai Hwa (Penerbit Universiti Kebangsaan Malaysia, 2020)
Eyewitness testimonies are significantly important in the forensic and legal domain; however, the emphasis on discrete emotions on the amount of misinformation reported by eyewitnesses remains relatively niche, warranting further scrutiny. The emotion fear in particular, has received scant attention and The Positive and Negative Affect Schedule (PANAS), has several limitations in capturing self-reports of discrete emotions. Therefore, this study aimed to investigate the effect of discrete emotions on the amount of misinformation reported. One hundred and eighty-eight undergraduate students were recruited and assigned to either the happy, sad, fearful or neutral condition. Participant’s responses were recorded on the Discrete Emotions Questionnaire (DEQ) before and after the emotion induction, and subsequently presented with a misinformation paradigm. Generally, it was proposed that; participants in the fearful condition would report the most amount of misinformation, followed by the neutral, sad and happy conditions, and participants across all conditions would report more misinformation on peripheral compared to central details. Experimental data analysis revealed there was no significant effect of discrete emotions on amount of misinformation reported. Hence, none of the hypotheses were supported. Despite these findings, this study captures the interesting facets of discrete emotions and provides a compelling forefront for future research.